1998
DOI: 10.1021/om9808054
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Pyridinium Acceptors via Thermal and Photoinduced Electron Transfer in Charge-Transfer Salts with Organoborates

Abstract: Colored salts of pyridinium tetraalkylborates [Py +,BR4 -] are readily isolated by the metathesis of LiBMe4, LiBMePh3, or NaBPh4 with a series of pyridinium triflates in aqueous solution. The interionic charge-transfer (CT) interaction between the organoborate anions and the pyridinium cations is established by their characteristic charge-transfer absorption bands and X-ray crystal structures. Thermal and photochemical CT activations of the salts lead to efficient methyl transfer from tetramethylborate (or met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 56 publications
4
21
0
1
Order By: Relevance
“…Indeed, we recently found that alkylation of pyridinium acceptors by tetramethylborate proceeds via an initial electron transfer to establish the significance of the electron-donor property of tetramethylborate in the formal transfer of an alkyl ligand. 3 As such, a question arises as to whether the transition-metal counterparts can behave in a similar manner. Although the mechanistic dichotomy between nucleophilic addition and electron transfer in the alkylcuprate addition to electrophiles has been addressed, 4 the electron-transfer reactivities of transition-metal alkylmetalates, in general, have been greatly hampered by their thermal instability and air sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we recently found that alkylation of pyridinium acceptors by tetramethylborate proceeds via an initial electron transfer to establish the significance of the electron-donor property of tetramethylborate in the formal transfer of an alkyl ligand. 3 As such, a question arises as to whether the transition-metal counterparts can behave in a similar manner. Although the mechanistic dichotomy between nucleophilic addition and electron transfer in the alkylcuprate addition to electrophiles has been addressed, 4 the electron-transfer reactivities of transition-metal alkylmetalates, in general, have been greatly hampered by their thermal instability and air sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the tetramethylaurate(III) anions have an ideal square-planar structure with a slight distortion of bond angles, 10,13 the C−Au−C bond angles between the cis methyl groups being 88. 3(2) and 91.7(2)° in one anion moiety and 89.17 (12) and 90.83(12)° in the other (Table 1)…”
Section: Introductionmentioning
confidence: 99%
“…[42] Durch Spin-Spin-Kopplung von 11 [70] mit Me 3 N-BH 2 CH 3 (CH 3 = 0.24 ppm, br s) [107] und B(CH 3 ) 4 À (d = À0.7 ppm, 2 J B-H = 4 Hz). [108] 9.4.…”
Section: Anionenunclassified
“…In addition, Zinckes salt of isoquinoline [366; R¼ 2,4-(NO 2 ) 2 C 6 H 3 ] may be transformed into chiral isoquinolinium salts [484] by reaction with chiral amines and the products are then reacted with Grignard reagents to afford 1,2-dihydroisoquinolines diastereoselectively [485]. N-Alkylisoquinolinium tetraalkylborates (366; R ¼ Me, X ¼ BMe 4 ) transfer alkyl groups efficiently under thermal or photochemical activation to give 370 (Scheme 17.172) [486]. On the other hand, the enantioselective addition of chiral allylsilanes activated by silver salts to an Nacylisoquinolinium cation has been reported to give 1-allyl-1,2-dihydroisoquinolines [487].…”
Section: Electrocyclic and Photochemical Reactionsmentioning
confidence: 99%